1997
DOI: 10.1007/bf02936952
|View full text |Cite
|
Sign up to set email alerts
|

Enteric-coated peppermint-oil capsules in the treatment of irritable bowel syndrome: A prospective, randomized trial

Abstract: To determine the efficacy and tolerability of an enteric-coated peppermint-oil formulation (Colpermin), we conducted a prospective, randomized, double-blind, placebo-controlled clinical study in 110 outpatients (66 men/44 women; 18-70 years of age) with symptoms of irritable bowel syndrome. Patients took one capsule (Colpermin or placebo) three to four times daily, 15-30 min before meals, for 1 month. Fifty-two patients on Colpermin and 49 on placebo completed the study. Forty-one patients on Colpermin (79%) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 9 publications
5
124
0
1
Order By: Relevance
“…The authors finally asserted the need for more accurate knowledge about the efficacy and safety of herbal medicines in pregnancy (Holst, Wright, Haavik, & Nordeng, 2009). In addition, while patients generally take herbal supplements in combination with conventional drugs (Liu et al, 1997;Abebe, 2002), some researchers discuss that herbal medicines should be cautiously administered to prevent any possible adverse drug-herb interactions or complications such as bleeding (Hepner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The authors finally asserted the need for more accurate knowledge about the efficacy and safety of herbal medicines in pregnancy (Holst, Wright, Haavik, & Nordeng, 2009). In addition, while patients generally take herbal supplements in combination with conventional drugs (Liu et al, 1997;Abebe, 2002), some researchers discuss that herbal medicines should be cautiously administered to prevent any possible adverse drug-herb interactions or complications such as bleeding (Hepner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent review included 5 trials for a total of 482 patients (107)(108)(109)(110)(111); it showed a statistically significant positive effect of peppermint oil versus placebo, with a NNT of 3 (95% CI: 2-4) (90). However, there was significant heterogeneity among studies.…”
Section: Efficacymentioning
confidence: 99%
“…1,2 One of the significant pathophysiology of IBS is visceral hypersensitivity, which has been known to have both mechanical and chemical causes. Because postprandial gastrointestinal symptoms have been reported to develop in a significant number of patients following consumption of spicy food, Gonlachanvit et al, 2 conducted a randomized, crossover study feeding subjects with and without IBS subjects and found that IBS patients were significantly more likely to exhibit hypersensitivity when chili, both in pill form and in food form, was consumed.…”
Section: Introductionmentioning
confidence: 99%